Effects of Er, Cr: YSGG Laser on Shear Bond Strength of the Orthodontic Brackets for 5 and 10 Seconds: An In Vitro Study - Ahmed A. Bagwan; Amal H. Abuaffan; Ali Alrahlah; Talat Hassan AL-Gunaid (Hindawi Limited, 2022)
Objectives. The study designed to compare the effect of erbium, chromium: yttrium-scandium-gallium-garnet (Er, Cr: YSGG) laser at different power outputs and short periods of time (5 and 10 s) and acid etching on the shear bond strength (SBS) and failure mode of metallic orthodontic brackets. Material and methods. A total of sixty-nine human premolars extracted for orthodontic purposes were used. 60 teeth were randomly assigned to one of the five treatment groups. (n = 12): group 1: 37% phosphoric acid etching and groups 2-5: the enamel surface irradiated by the Er, Cr: YSGG laser operated at different power outputs (1 W, 1.5 W, 2 W, and 2.5 W), each laser group was divided into two subgroups (n = 6) according to exposure time (5 s and 10 s). Nine teeth were not subjected to SBS testing but were prepared for scanning electron microscopy (SEM). The nonparametric Kruskal-Wallis test was used to evaluate the data; the SBS and adhesive remanent index (ADI) were evaluated. Results. The mean SBS for all laser groups and the acid-etched group were comparable, with no significant differences except for the 1 W group for 5 and 10 s and the 1.5 W group for 5 s. For the ARI scores, no statistically significant difference was found among the groups (P=0.059), and the majority of the samples had ARI type 2 or 3. Conclusion. The laser irradiation at 2 and 2.5 W for 5 s was similar to that produced by acid etching, whereas the laser irradiation at 2 and 2.5 W at 10 s was higher compared with that obtained with acid etching and adequate to etch the enamel.